A10 TR1 CELL-BASED THERAPY FOR INFLAMMATORY ILEITIS IN SHIP-/- MICE. (26th February 2020) - Lisko, D; Menzies, S; Sly, L M; Steiner, T
Abstract: Background: Crohn's disease (CD), a form of inflammatory bowel disease (IBD), is characterized by chronic inflammation that can occur anywhere along the gastrointestinal (GI) tract, but commonly involves the distal portion of the ileum. Src homology 2 (SH2) domain-containing inositol polyphosphate 5-phosphatase 1 (SHIP) is a hematopoietic-specific regulator of secondary signals generated by the PI3K pathway and regulates immune activation. SHIP -/- mice, at 6–8 weeks of age, spontaneously develop inflammatory ileitis due to myeloid proliferation, a lack of T cells, and an increase in IL-1β. Aims: Here we investigated the efficacy of type 1 regulatory T (Tr1) cells, which are characterized by high IL-10 production, a broadly acting anti-inflammatory cytokine that promotes gut homeostasis, to treat ileitis in SHIP -/- mice. Methods: Using IL-10 GFP FOXP3 RFP B6 reporter mice, we sorted FOXP3 - CD44 High Tr1 cells, FOXP3 + Tregs, and FOXP3 - CD44 Low naive T cells from total CD4 + T cells, and cultured them with immobilized α-CD3, soluble α-CD28 and recombinant IL-2 for 3 days. Naive T cells were grown in undifferentiated conditions or polarized to Th1 or Th17 cells. Cell phenotypes were characterized by ELISA and flow cytometry. For the adoptive Tr1 cell transfer, CD44 High cells were sorted from FOXP3 GFP Thy1.1 reporter mice and cultured as above with an additional 2 days' rest in the presence of IL-2 alone. SHIP -/- mice and wild type (WT) littermates were sublethally irradiated at 5 weeks of age, followed 24h later by IP injection with 0.7 – 1.0 x 10 6 Tr1 cells or PBS vehicle. At 7 weeks of age, mice were euthanized and blood, mesenteric lymph nodes (MLNs), and ileal tissue were processed. Results: After 3 days of stimulation, FOXP3 - CD44 High Tr1 cells produced more IL-10 than Tregs and less IFN-γ than Th1 cells. Additionally, CD44 High cells had higher co-expression of CD49b and Lag3, biomarkers for Tr1 cells, in comparison to nT cells, Tregs, Th1, and Th17 cells, a higher percentages of IL-10 producing cells than FOXP3 + Tregs and produced less IFN-γ, IL-17, and TNF-α in comparison to Th1, Th17 and naive T cells, respectively. We found that Tr1 cells successfully engrafted irradiated SHIP -/- mice. Furthermore, engrafted Tr1 cells had high co-expression of CD49b and Lag3, with the majority of these cells located in the MLNs and spleen. SHIP KO mice that received Tr1 cells had comparable ileal length and appearance to SHIP WT, and significantly longer ilea versus SHIP PBS controls — indicating decreased inflammation as a result of successful engraftment. Conclusions: In conclusion, ex-vivo expansion and adoptive transfer of Tr1 cells to SHIP -/- mice led to cellular engraftment and improvement in spontaneous ileitis. Hence, Tr1 cellular therapy shows promise as a therapeutic approach in CD. Future experiments will be needed to determine the therapeutic dose range of Tr1 cells and the mechanisms of protection. Funding Agencies: CCC